Examining the Link between Ethical Culture and Integrity Violations: The Mediating Role of Integrity Climate - Izzaz Zahari, Afzal; Said, Jamaliah; Arshad, Roshayani (KnE Social Sciences, 2019)
Integrity violations are actions that can cause harm to the economy and society at large. These violations would cost the organisation losses or devalue their reputation. Many initiatives were taken to mitigate integrity violations at the organisation level. Creating a positive ethical culture was argued as a crucial approach to minimise the incident of integrity violations. However, to date, little research was done to provide empirical support on whether ethical culture contributes significant effect to integrity violation. This paper aims to investigate whether ethical culture can impact integrity violations. Data were collected using questionnaires distributed to 459 state government departments. There are a total of 343 out of 459 (75%) questionnaires distributed to Malaysian state government departments were received. The findings indicate that integrity climate mediates the relationship between ethical culture and integrity violations. The practicality of the research provides a further understanding of public sector organisations and their behaviours. The viewpoint of whether having ethical culture as a social norm in an organisation provides insight towards the occurrence of integrity violations.